Disclosure of Assets of the Agricultural Enterprises in the Financial Reporting under International Financial Reporting Standards - Shumakova, Oksana Viktorovna; Blinov, Oleg Anatolyevich; Khrabrykh, Sergey Leonidovich; Mozzherina, Tatyana Gennadyevna; Kryukova, Olga Nikolaevna (International Journal of Economics and Financial Issues, 2016)
The subject of the research is the set of theoretical and practical approaches to the recognition of assets of the agricultural enterprises of the Omsk region in the accounting under IFRS. The research objective is the development of an optimal testing model of assets of the agricultural enterprises for compliance with IFRS. The study was conducted on the basis of financial statements prepared under the Russian Financial Reporting Standards. The three asset items with the largest share were allocated in the statements: fixed assets, inventories and accounts receivable. The most essential items were allocated as part of fixed assets: machinery and equipment and agricultural products respectively. Accounts receivable were tested for compliance with IFRS. The calculation of market price taking into account the correction factor in question considering the technical condition of vehicles was performed upon testing of machinery and equipment. The calculation of net realizable value based on market prices for the products was performed upon testing of machinery and equipment. The market-value appraisal of the receivable by discounted cash flows was performed upon testing. The proposed testing method has a practical value. It can be used in the preparation of financial statements under IFRS, on the basis of financial statements prepared in accordance with the Russian Financial Reporting Standards. It has been established that the machinery and equipment and agricultural products are reflected in the financial statements in accordance with IFRS. Because of overdue accounts the accounts receivable are substantially overstated. Keywords: international financial reporting standards, agricultural enterprises, accounting statements. JEL Classifications: M41, O18